Pastoral da juventude: análise atual da acolhida e do acompanhamento de grupos de jovens católicos na República Dominicana - Lora, Juan Andrés Hidalgo (2011)
This dissertation is based on the worldwide evident withdrawal of the youths from the catholic churches. The new structures and the unquestionable realities of the post-modern world, mainly the multitechnological world, demand a review of their pastoral regarding the youths, forsaking archaic structures while searching for the new evangelical. First we need to know the world of the youths, their aspirations, dreams and difficulties to reach their goals in life. The youths are innately full of emotions, open-minded and long for comradeship. Here is where religions in general have the mission to make them discover the shining path of the soul. Based on experts who have studied this crisis and supported by researches carried out in a parish of the Dominican Republic as a sample, we propose a brotherly welcome and a subsequent follow-up programme for the youths as a possible solution for this impasse. The awareness of their constituting elements and the deep study of their aggregative psychology can help the youths to ponder upon their dignity as sons of God